2005
DOI: 10.1038/sj.onc.1208435
|View full text |Cite
|
Sign up to set email alerts
|

RKIP downregulates B-Raf kinase activity in melanoma cancer cells

Abstract: The Raf-MEK-ERK protein kinase cascade is a highly conserved signaling pathway that is pivotal in relaying environmental cues from the cell surface to the nucleus. Three Raf isoforms, which share great sequence and structure similarities, have been identified in mammalian cells. We have previously identified Raf kinase inhibitor protein (RKIP) as a negative regulator of the Raf-MEK-ERK signaling pathway by specifically binding to the Raf-1 isoform. We show here that RKIP also antagonizes kinase activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 20 publications
7
90
0
1
Order By: Relevance
“…The effect of Snail on RKIP was on the level of transcriptional initiation and mediated by a proximal E-box on the RKIP promoter. (Chatterjee et al, 2004;Park et al, 2005). Consistent with its demonstrated inhibitory effect on Raf and NF-kB signaling, we and others have shown that the expression levels of RKIP are downregulated in a number of tumors, including highly metastatic prostate, breast and colon cancer, hepatocellular carcinoma, melanomas and insulinomas (Fu et al, 2003;Chatterjee et al, 2004;Schuierer et al, 2004Schuierer et al, , 2006Zhang et al, 2004;Hegan et al, 2005;Al-Mulla et al, 2006;Lee et al, 2006).…”
supporting
confidence: 72%
“…The effect of Snail on RKIP was on the level of transcriptional initiation and mediated by a proximal E-box on the RKIP promoter. (Chatterjee et al, 2004;Park et al, 2005). Consistent with its demonstrated inhibitory effect on Raf and NF-kB signaling, we and others have shown that the expression levels of RKIP are downregulated in a number of tumors, including highly metastatic prostate, breast and colon cancer, hepatocellular carcinoma, melanomas and insulinomas (Fu et al, 2003;Chatterjee et al, 2004;Schuierer et al, 2004Schuierer et al, , 2006Zhang et al, 2004;Hegan et al, 2005;Al-Mulla et al, 2006;Lee et al, 2006).…”
supporting
confidence: 72%
“…There was no evidence of similar responses in V600E transfectants, providing no clear basis for the observed survival inhibition. Similarly there was no detectable change in the phosphorylation status of p38 MAPK (not shown), and no change in levels of RAF kinase inhibitor protein (RKIP; Figure 4), a recently reported negative regulator of RAF-1 and B-RAF kinases (Park et al, 2005). However, six days after induction of IGF1R gene silencing there was clear suppression of Akt phosphorylation in all three transfected CHL-1 cell populations (Figure 4b).…”
Section: Igf1r Targeting In V600e B-raf Melanomamentioning
confidence: 59%
“…Whether spindle checkpoint functions of RKIP are exerted through Raf-1 or B-Raf signaling remains uncertain since RKIP can inhibit either Raf-1, 42,43 or B-Raf signaling. 44 Depletion of Raf-1 was shown to rescue the RKIP depletion phenotype whereas Raf-1 overexpression mimicked the RKIP depletion phenotype, 13 suggesting that RKIP might exert its effects through Raf-1. In contrast, overexpression of a constitutively active B-Raf mutant (B-Raf V600E ) in melanoma cells delays mitotic progression by hyper-activation of the mitotic checkpoint.…”
Section: Methodsmentioning
confidence: 99%